Pengaruh Metode Talaqqi terhadap Kualitas Hafalan Santri Putri Pesantren Al-Muslimun Plaosan Magetan - Aisyah Sausan Nadhifah; Murni Umi Salamah; Arya Hafiz Pratisena; Rusmi; Malika Hafidatul Ramadhan (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
The learning of Qur’anic memorization (tahfidz) requires an effective method that not only increases the quantity of memorization but also maintains the quality of recitation in accordance with the rules of tajwid and proper pronunciation of makharijul huruf. This research is important because many students are able to memorize a large number of verses, yet their recitation quality does not fully meet the expected standards. This study aims to examine the effect of the application of the talaqqi method on the quality of Qur’anic memorization of female students at Al-Muslimun Islamic Boarding School, Sumberagung, Plaosan, Magetan. The research employed a quantitative approach using an ex post facto research design. Data were collected through questionnaires distributed to female students participating in the tahfidz program and analyzed using normality tests and simple linear regression with the assistance of SPSS software. The findings indicate that the application of the talaqqi method has a significant effect on the quality of Qur’anic memorization, particularly in terms of accuracy of recitation, fluency of memorization, and correct articulation of makharijul huruf. Therefore, the talaqqi method is proven to be effective and relevant for improving the quality of Qur’anic memorization in Islamic boarding schools.